(untitled) (American Journal of Islam and Society, 2006)
David G. Atwill’s recent historical work joins in the anthropological stream of studying the ethnic groups of China’s Yunnan province. This book presents a history of the violence in nineteenth-century Yunnan, to which ethnicity, economics, culture, environment, and politics all contributed. It consists of ten chapters, the first of which discusses the bloody history of the Hui (Muslim) genocide by the Han (Chinese). In this chapter, Atwill identifies why the Han resent the Hui and refutes conventional assumptions about the Panthay rebellion (1856-72). The second chapter situates nineteenth-century Yunnan in mosaic landscapes of region, commerce, ethnicity, and geography and provides the context for understanding the ensuing violence. The third chapter presents the history, communities, and networks of Muslims in multiethnic Yunnan, and the fourth chapter discusses Han trouble-makers (Hanjianism) in Yunnan’s borderlands and presents a history of non-Han resistance to Han expansion. The fifth and sixth chapters concentrate on Han hostility toward the Hui and documents in detail the massacre of Muslims by Han officials and militia as well as major Hui resistance campaigns: rebellions in Yunnan’s eastern, southern, and western regions. The seventh chapter discusses divisions among Yunnan’s Hui, which were largely due to differences in region, religion, and personal ambitions, along with the Qing policy of using some Hui to control other Hui. The eighth chapter focuses on the Dali regime (1856- 72), which Atwill surprisingly labels as “Sultanate,” and discusses its multiethnic character. The ninth chapter presents the back-and-forth battles between the Dali Sultanate and the Qing, and the fall of the Dali regime. The tenth chapter, as an epilogue, critiques the existing scholarship, which fails to note the facts of the Han massacre of the Hui and the multiethnic backing of the Dali regime. It also restates that the Panthay rebellion was primarily a Hui-led indigenous multiethnic resistance to the Han immigrants’ hunger ...